Influence of fetal birth weight on perinatal outcome in planned vaginal births - Temerinac, Dunja; Chen, Xi; Suetterlin, Marc; Kehl, Sven (Archives of Gynecology and Obstetrics, 2014)
The aim of this study was to provide information for better obstetric counseling by analyzing the impact of fetal birth weight (BW) on fetal and maternal outcome when vaginal birth is planned in a university hospital.In this retrospective study from January 1st 2006 to December 31st 2011, 5,177 singleton, alive deliveries at or >37 gestational weeks were assessed with regard to the fetal BW when vaginal birth was attempted. The normal BW group was defined as >=2,500 <4,500 g. For comparison, further BW groups were defined as: group 1 <2,500 g, group 2 >=4,000 <4,250 g, group 3 >=4,250 <4,500 g and group 4 >=4,500 g. Outcome criteria were mode of delivery and perineal lacerations as well as the pH and base excess of the umbilical cord artery, the Apgar score after 5 min and occurrence of shoulder dystocia. The set of controlling variables included maternal height, maternal weight, maternal age, gestational age, neonatal sex and parity.Second stage caesarean section is significantly more likely when fetal BW is under 2,500 g (30.7 vs. 15.5 % in the normal BW group, odds ratio 3.01, 95 % confidence interval 2.03-4.46, p value < 0.001). Shoulder dystocia occurred significantly more often when fetal BW was over 4,250 g (group 3: odds ratio 4.95, 95 % confidence interval 1.74-14.10, p value 0.003, group 4: odds ratio 19.96, 95 % confidence interval 7.61-52.38, p value < 0.001). The risk of an Apgar score after 5 min below 7 increased, when fetal BW was below 2,500 g (odds ratio 9.28, 95 % confidence interval 3.15-27.35, p value < 0.001) or above 4,500 g (odds ratio 5.65, 95 % confidence interval 1.22-26.24, p value 0.027). All groups were comparable to the normal group regarding pH and base excess of the umbilical cord artery as well as the risk for severe (third and fourth degree) perineal lacerations.Although a fetal birth weight under 2,500 g and a birth weight over 4,250 g are associated with some risks, there is no general contraindication for an attempt to deliver vaginally in a university hospital with regard to fetal birth weight.
EVALuna2:17531